Radioimmunbehandlung solitärer Lebermetastasen mittels intratumoraler Instillation 131J-markierter monoklonaler Antikörper - Erste Ergebnisse einer klinischen Studie - Müller-Gärtner, H.-W.; Montz, R.; Klapdor, R.; Hirschmann, M.; Rehpenning, W.; Langkowski, J. (Nuklearmedizin - NuclearMedicine, 1988)
Solitary liver metastases (carcinoembryogenic antigen positive) in two patients suffering from colon carcinoma were multifocally injected with 131I- labelled monoclonal antibodies (131I-MAb) against the carcinoembryogenic antigen (CEA). The 131I activity in the metastases decreased biexponentially. The131I serum concentration declined triexponentially in patient 1 and mono- exponentially in patient 2. The radiation dose to the whole tumor volume amounted to 358 Sv and 762 Sv, respectively; the whole-body radiation dose was 87.5 mSv for patient 1 and 39.0 mSv for patient 2. Complications did not occur. Before treatment there had been a volume doubling time of the metastases of 1.5 and 0.9 months, respectively; this contrasts with a constant tumor volume after treatment as observed over the follow-up period of 3.5 and 2 months, respectively. The CEA serum concentration decreased after131I-MAb instillation within 1.5 and 2.5 months to 66% and 58%, respectively, when compared with values immediately before treatment. On the basis of these results the intratumoral application of 131I-MAb appears in selected cases to be a suitable method of slowing down growth of liver metastases from gastrointestinal tumors.